Chemical and Organoleptic Quality of Kombucha Tea at Different Fermentation Time and Concentration of Cherry Leaves (Muntingia calabura L.) - Josephine C.P.K.; Fadjar Kurnia Hartati; Bambang Sigit (Demeter: Journal of Farming and Agriculture, 2023)
The leaves of the cherry plant (Muntingia calabura L.) contain vitamin C and phenolic compounds. High phenolic compounds have the potential to have antioxidants. Efforts to increase antioxidant activity can be carried out by fermentation using SCOBY. The purpose of this study was to determine the effect of cherry leaf concentration and fermentation time on the chemical and organoleptic quality of cherry leaf kombucha tea, and to determine the best treatment for cherry leaf kombucha tea. This study used a completely randomized design (CRD) which was arranged in a factorial manner with 2 factors. The first factor is the fermentation time with 3 levels (4 days, 8 days, 12 days). The second factor is the concentration of cherry leaves with 3 levels (1%, 2%, 3%). Each treatment combination was repeated 3 times. The chemical analysis of cherry leaf kombucha that will be tested is the total phenol content using the Folin Ciocalteau reagent with the spectrophotometric method, antioxidant activity with the DPPH method, and vitamin C with the iodine titration method. Analysis of organoleptic quality was carried out by testing the level of preference / hedonic test which included color, aroma, and taste. Determination of the best treatment is done by using the effectiveness test. K3L2 treatment with 3% cherry leaf concentration and 8 days of fermentation gave the best treatment results, namely 0.71, which means that this treatment is the best treatment with parameter criteria including antioxidant 109.77 ppm, phenol 9.42 mg GAE/g, vitamin C 22.92 ppm, taste 3.85 (neutral), scent 3.00 (rather dislike), and color 5.00 (rather like)